2021
DOI: 10.1002/hep4.1634
|View full text |Cite
|
Sign up to set email alerts
|

Direct-Acting Antiviral Treatment Use Remains Low Among Florida Medicaid Beneficiaries With Chronic Hepatitis C

Abstract: Medicaid prior authorization (PA) policies for treatment of hepatitis C virus (HCV) with direct‐acting antiviral (DAA) therapy are changing. We aimed to evaluate effects of changes in PA requirements on treatment uptake and to determine the factors associated with DAA treatment among Florida Medicaid beneficiaries with HCV. This is a retrospective cohort analysis of Florida’s Medicaid administrative claims and electronic medical records (2013‐2018). A total of 14,063 newly diagnosed patients with HCV were grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 37 publications
2
31
0
Order By: Relevance
“…9,10,12,24,25 Patient-level barriers include poor knowledge of HCV, stigma associated with having HCV, mental health issues, and general challenges with accessing the health care system. 23,26 On the other The low treatment initiation in the SUD population may be due to factors such as patients' refusal, physicians' concerns, and payer's rejection/rigid eligibility criteria which appears to be most relevant to those who was similar to other recent studies which also showed that among those with SUDs those that started treatment were highly likely to complete treatment and to obtain a cure. 25,33,34 We found that those whose treatment regimens included RBV were almost four times as likely to discontinue therapy regardless of their SUD status as those who did not have RBV as part of their therapy.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…9,10,12,24,25 Patient-level barriers include poor knowledge of HCV, stigma associated with having HCV, mental health issues, and general challenges with accessing the health care system. 23,26 On the other The low treatment initiation in the SUD population may be due to factors such as patients' refusal, physicians' concerns, and payer's rejection/rigid eligibility criteria which appears to be most relevant to those who was similar to other recent studies which also showed that among those with SUDs those that started treatment were highly likely to complete treatment and to obtain a cure. 25,33,34 We found that those whose treatment regimens included RBV were almost four times as likely to discontinue therapy regardless of their SUD status as those who did not have RBV as part of their therapy.…”
Section: Discussionmentioning
confidence: 63%
“…Patients were considered to have discontinued early if the observed treatment duration (summing the number of days from the filling of the first prescription to the end date of the last prescription claim fill date plus days' supply) was shorter than the expected treatment duration (a 30-day gap was allowed as discussed in prior studies). [21][22][23] The expected treatment duration was based on the 2017 AASLD/IDSA HCV treatment guidelines accounting for baseline cirrhosis diagnosis. 21 For example, we used 8 weeks for sofosbuvir/ < 0.001).…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…51 Second, given the current reimbursement requirements, it is possible that our population might have had to abstain from alcohol or injectable drug use for a certain period of time to be able to obtain the insurance approvals necessary to cover the costs of DAA treatment. 29,65 Thus, our DAA group may have been more likely to be former substance users, but our non-DAA group may have been more likely to be current substance users. We attempted to mitigate this limitation by controlling for SUD-related ED or inpatient visits at baseline.…”
Section: Discussionmentioning
confidence: 98%
“…24,25 Despite these recommendations, access to DAAs for patients with SUD and chronic HCV has still been limited. [26][27][28][29] This divergence from the AASLD/IDSA clinical guidelines for patients with SUD and chronic HCV may reflect concerns of payers and providers. [29][30][31] Concerns regarding high prescription DAA costs have led private and public payers to restrict access to these medications, requiring that patients meet specific prior authorization approvals.…”
Section: What This Study Addsmentioning
confidence: 99%
See 1 more Smart Citation